Persepsi, Minat, Pengetahuan tentang Pajak, dan Pemahaman Trikon Terhadap Pilihan Berkarir dibidang Perpajakan - Nova Vajarini (Yayasan Literasi Ilmiah Indonesia, 2021)
Purpose : The purpose of this research is to examine perceptions, interests, knowledge of taxes and understanding of Trikon towards career choices in the field of taxation.Method: In this study, the researcher took a sample of accounting students in the 2018 and 2019 years at the Faculty of Economics, University Sarjanawiyata Tamansiswa who are still actively studying and have taken Taxation and Student Affairs courses. The number of respondents obtained as many as 111 students. This test uses the classical assumption test, normality test, and multiple linear regression.Finding: Tax perception has a positive effect on career choices in taxation, interest does not affect career choices in taxation, tax knowledge does not affect career choices in taxation, understanding of Trikon affects students' choice of careers in taxation.Novelty: The novelty in this research is the addition of a trikon understanding variable to prove how students can practice Ki Hajar Dewantara's teachings in career specialization in the field of taxation.